Correlations between temperament and biological sex and gender schema - Korzeń, Renata (Studia Psychologica: Theoria et praxis, 2007)
The participants (327 female and 306 male, students of Warsaw high schools) filled in IPP and EAS-D. The results of research show that biological sex, gender schema and temperament are connected. Men more often have I type of temperament (non-emotional, social active) and women more often have II type of temperament (emotional, social active). Feminine women and men have high level of fear and low level of activity. Undifferentiated women and men are less active and less sociable than another genders. Androgyny women and men present high activity and high sociability.